Optimising endurance training of elite cyclists by inclusion of sprints during low-intensity sessions - Almquist, N. W. (2020)
Paper 1: Almquist, N.W., Ettema, G., Hopker, J., Sandbakk, O., Rønnestad, B.R. The Effect of 30-Second Sprints During Prolonged Exercise on Gross Efficiency, Electromyography, and Pedalling Technique in Elite Cyclists. International Journal of Sports Physiology and Performance. 2019:1-9. This article is not included due to copyright restrictions.